PERAN CAMAT DALAM HUBUNGAN KERJA DENGAN APARAT DI KANTOR KECAMATAN SARIO KOTA MANADO - RIMBING, FALENTINO FHEGZAL; RUMAPEA, PATAR; RARES, JOYCE JACINTA (JURNAL ADMINISTRASI PUBLIK, 2018)
This research explains about the role of sub-district head in working relationship with apparatus in subdistrict office of Sario of Manado City in creating harmonious, balanced and integrity of workingrelationship in performing their duties. Role is the behavior expected of someone who has position in anorganization. The sub-district head as a leader carries out his duties and functions to organize the subdistrict and coordinating with the apparatus. The duties and functions of sub-district heads are regulatedbased on Law Number 23 of 2014 on Regional Government. This research uses descriptive method ofqualitative approach, and data collection technique done by observation, interview technique anddocumentation. Number of informants as many as 10 people. The role of sub-district heads in workingrelationships with apparatus is assessed using behavioral theory according to Benjamin Bloom, which inbehavior includes 3 indicators: (i) knowledge; (ii) attitudes; and (iii) actions. The result of this researchindicates that the role of sub-district heads in working relationships with the apparatus was good enough,but still have a lacked in the delivery of information and the development to the apparatus. Which in thesubmission of the information of the sub-district head does not review the information submitted and thedevelopment to an undisciplined apparatus has not been firmly because the sub-district head is moreconcerned with informal relationships than the organization's interest in the Sub-district Office of Sario.Keywords: Role, Working Relationship